Pelatihan Diversifikasi Olahan Ikan Bandeng Upaya Peningkatan Ekonomi Produktif Masyarakat di Kelurahan Untia Kecamatan Biringkanaya - Deselfia DNM Sahari; St. Syahriati; Andi Herlina; Darwis Darwis; Abbas Abbas (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Milkfish is one of the potential fishery products in untia village, biringkanaya sub-district. The abundant production of milkfish causes the selling price of fresh milkfish to be cheaper, besides that fresh milkfish is also prone to damage if stored for too long. The lack of understanding and skills of the local community in processing milkfish is the main obstacle faced by the community. The purpose of this service is training on diversification of milkfish preparations to improve the productive economy of the community in untia village, biringkanaya sub-district. The method of implementing community service activities is through counseling and training. This counseling is a way to convey knowledge to housewives about the benefits, nutritional content and potential of milkfish. Training with the practice of making shredded milkfish, The results of community service activities are the growth of an entrepreneurial spirit for local housewives and training community creativity in giving innovation by producing new products that have economic value.